Greasing the wheels?: the impact of regulations and corruption on firm entry - Dreher, Axel; Gassebner, Martin (Public choice, 2013)
This paper investigates the question of whether corruption might ‘grease the wheels’ of an economy. We investigate whether and to what extent the impact of regulations on entrepreneurship is dependent on corruption. We first test whether regulations robustly deter firm entry into markets. Our results show that the existence of a larger number of procedures required to start a business, as well as larger minimum capital requirements are detrimental to entrepreneurship. Second, we test whether corruption reduces the negative impact of regulations on entrepreneurship in highly regulated economies. Our empirical analysis, covering a maximum of 43 countries over the 2003-2005 period, shows that corruption facilitates firm entry in highly regulated economies. For example, the ‘greasing’ effect of corruption kicks in at around 50 days required to start a new business. Our results thus provide support for the ‘grease the wheels’ hypothesis.